Organo-catalytic approach to the enantioselective synthesis of (R)-selegiline - Talluri, Siva Kumar; Sudalai, Arumugam (Tetrahedron, 2007)
An efficient enantioselective synthesis of (R)-selegiline has been achieved by two routes, via proline-catalyzed alpha-aminooxylation as well as alpha-amination of phenylpropanaldehyde as the key step. (c) 2007 Elsevier Ltd. All rights reserved.